Profitability Moderation on the Effect of Tax Avoidance on Company Value - Ria (PT FORMOSA CENDEKIA GLOBAL, 2023)
Taxes are a burden on corporations that eat into corporate profits, whereas taxes on a country are revenues that are used to pay for government spending. These differences motivate companies to manage their tax liabilities. Corporate values ​​are also influenced by high corporate profitability. The purpose of the study is whether tax avoidance affects firm value and whether weakening profitability increases the effect of tax avoidance on firm value. The study will be conducted from April 1 to July 1, 2022. The underlying theories of this research are agency theory and signaling theory. The subjects of this study include 14 multinational companies registered on the Indonesian Stock Exchange during the period 2017-2021, representing a sample of 70 companies. The data analysis techniques used were descriptive, pooled, classical hypothesis testing, simple linear regression analysis test, moderate regression analysis (MRA), test f, test t, and r2. Data obtained from (www.idx.co.id) and (www.idnfinancials). Research shows that tax avoidance has a significant positive impact on firm value. At the same time, modest profitability does not significantly increase the effect of tax avoidance on firm value